Gender-based analysis of stress factor among Universiti Teknologi MARA (UiTM) students / Syarul Heiry Yahaya ... [et al.] - Yahaya, Syarul Heiry; Umar, Norazah; Kadar, Rozita; Ab Rahman Muton, Nursakirah (UiTM Cawangan Perlis, 2024)
Today, stress often becomes a significant problem in the daily life. Various factors contribute to this mental health issue, including a busy lifestyle, work pressure, financial issues, health concerns, tense interpersonal relationships, technological advancements, and social changes. In the tertiary education especially, stress can significantly affect students’ mental health and this can impact their performance in academic study. The stress level may impact differently between gender, this is due to some factor that are unique to female students’ experiences such as social pressure, hormonal factor or safety concern. This research is focus during the post covid19 where students are studying in hybrid mode which is online and also face to face for certain subjects they learn in university. This research aims to see the differences in the mean stress score by gender and also the relationship between level of stress and gender by using Depression Anxiety Stress Test (DASS) questionnaire. The data of the questionnaire are collected during online webinar and analyzed based on the objective of this research. The results from this research study indicate that there is a difference in the mean score by gender, and the relationship between stress level and gender is significant.